2013
DOI: 10.1111/bjh.12602
|View full text |Cite
|
Sign up to set email alerts
|

Secondary cancers among children with acute lymphoblastic leukaemia treated by the Tokyo Children's Cancer Study Group protocols: a retrospective cohort study

Abstract: SummaryWith improvement in survival, it is important to evaluate the impact of treatment on secondary cancers in acute lymphoblastic leukaemia (ALL) survivors. A retrospective cohort study comprising 2918 children diagnosed with ALL and enrolled on Tokyo Children's Cancer Study Group (TCCSG) protocols between 1984 and 2005 was conducted to evaluate the incidence of secondary cancers and associated factors including treatment protocol, cranial irradiation and other characteristics of the primary ALL. Thirtyseve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…In Japan, a retrospective cohort study of 2,918 children who received a diagnosis of acute lymphoblastic leukemia (ALL), the most common pediatric malignancy, evaluated the incidence of secondary malignancies and associated factors such as treatment protocols, cranial irradiation (CRT), and other characteristics of primary ALL. The cumulative incidence of all secondary malignancies was 1.0% at 10 years and 2.4% at 20 years 7 . Furthermore, Ishida et al reported that, among 5,387 patients from 15 centers in Japan who survived primary pediatric malignancies, 128 (2.4%) developed secondary malignancies.…”
Section: Introductionmentioning
confidence: 94%
“…In Japan, a retrospective cohort study of 2,918 children who received a diagnosis of acute lymphoblastic leukemia (ALL), the most common pediatric malignancy, evaluated the incidence of secondary malignancies and associated factors such as treatment protocols, cranial irradiation (CRT), and other characteristics of primary ALL. The cumulative incidence of all secondary malignancies was 1.0% at 10 years and 2.4% at 20 years 7 . Furthermore, Ishida et al reported that, among 5,387 patients from 15 centers in Japan who survived primary pediatric malignancies, 128 (2.4%) developed secondary malignancies.…”
Section: Introductionmentioning
confidence: 94%
“…Both chemotherapeutic agents and irradiation are potentially genotoxic and may cause secondary malignancy in patients treated with these modalities. Indeed, there are both international and Japanese reports describing secondary cancer . The treatment of leukemia also causes other long‐term sequelae such as chronic health disorders and neurobehavioral problems in cancer survivors .…”
Section: Long‐term Follow Upmentioning
confidence: 99%
“…Indeed, there are both international and Japanese reports describing secondary cancer. 51,56 The treatment of leukemia also causes other long-term sequelae such as chronic health disorders and neurobehavioral problems in cancer survivors. 57 Systematic monitoring of ALL survivors should thus be conducted comprehensively.…”
Section: Long-term Follow Upmentioning
confidence: 99%
“…However, long-term survivors of childhood ALL are also at risk for the development of a secondary neoplasm [7131423]. A recent investigation in Japan has found secondary neoplasms development in 37 (2.2%) of 1,716 patients treated after a diagnosis of ALL within a median follow-up duration of 9.5 years [14]. The types of secondary neoplasms in these patients includes hematologic malignancies (acute myeloid leukemia, myelodysplastic syndrome and non-Hodgkin lymphoma), brain tumors and other solid carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Whether, in individual cases, the development of a secondary neoplasm is related to the treatment of the previous one is uncertain, because genetic risk factors or other external carcinogens may also be involved. However, it is certain that the risk of a secondary neoplasm developing in patients treated for ALL is higher than that of the normal population and, in fact, a variety of secondary neoplasms, such as brain tumors, hematologic malignancies, sarcomas, thyroid cancers, and skin cancers have been reported in the literature [7131423]. Radiation effects are generally accepted to be a crucial factor in the development of the secondary neoplasm, but the exact mechanism by which this occurs remains unclear [29].…”
Section: Introductionmentioning
confidence: 99%